Pengembangan LKPD Berbasis Peduli Lingkungan Pembelajaran IPAS Bab 2 Topik C pada Kelas V SDN Banyuajuh 5 Kabupaten Bangkalan - Debby Rahmawati; M. Fadlillah (Jurnal Pengembangan dan Evaluasi Pendidikan, 2024)
The objectives of this development research are (1) to determine the validity of the development of environmentally-conscious student worksheets (LKPD); and (2) to assess the attractiveness of these environmentally-conscious LKPDs. These worksheets are used as supplementary teaching materials based on environmental themes for the fifth-grade class at SDN Banyuajuh 5 Bangkalan. This development research employs the 4D model. The subjects of the research are 22 students. Based on expert validation results, the following percentages were obtained: 95% from material experts, 82.5% from language experts, 87.5% from instructional design experts, and 90% from teaching material design experts. The average result of these validations is 88.75% (very valid). The attractiveness of the LKPD was measured through teacher response questionnaires regarding the environmentally-conscious LKPD. The questionnaire results showed that teachers gave a percentage of 95%, placing the LKPD in the category of very attractive teaching materials. Based on the research results, the environmentally-conscious LKPD for the Science and Social Studies (IPAS) course, Chapter 2, Topic C, conducted at SDN Banyuajuh 5 Bangkalan, is deemed valid and attractive for use as supplementary teaching material in the learning process.